2021
DOI: 10.3390/geosciences11110458
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nine Operational Models in Forecasting Different Types of Synoptic Dust Events in the Middle East

Abstract: This study investigates four types of synoptic dust events in the Middle East region, including cyclonic, pre-frontal, post-frontal and Shamal dust storms. For each of these types, three intense and pervasive dust events are analyzed from a synoptic meteorological and numerical simulation perspective. The performance of 9 operational dust models in forecasting these dust events in the Middle East is qualitatively and quantitatively evaluated against Terra-MODIS observations and AERONET measurements during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 120 publications
(193 reference statements)
0
14
0
Order By: Relevance
“… 35 It is important to remark that Dasht Kavir and Lut deserts with complex topography and known as having strong seasonal winds that are directly responsible for atmospheric circulation of air movement the large-scale area. 36 However, complex topography creates ideal conditions for transport of pollutants due to weather conditions and long-range emissions. Particle matter (PM) is one of the most remarkable pollutants that has been emitted from various sources such as volcanos and seismic activities, wild-land fires and etc.…”
Section: Airmentioning
confidence: 99%
“… 35 It is important to remark that Dasht Kavir and Lut deserts with complex topography and known as having strong seasonal winds that are directly responsible for atmospheric circulation of air movement the large-scale area. 36 However, complex topography creates ideal conditions for transport of pollutants due to weather conditions and long-range emissions. Particle matter (PM) is one of the most remarkable pollutants that has been emitted from various sources such as volcanos and seismic activities, wild-land fires and etc.…”
Section: Airmentioning
confidence: 99%
“…Figure 5a shows diagrams of dust concentration and dust load referring to the end of that day, a few hours after the end of the lidar measurements. This is done in order to better reveal the height distribution of the dust concentration, for the purpose of comparing it with the lidar height profiles obtained by us, taking into account the space/time uncertainties of the model, particularly in the dust frontal area [34,[86][87][88]. The left-hand part of the color chart shows the wind field of the deep low from the northwest, which causes an extensive vortex in the region of Southwestern Sahara over the territories of Western Sahara, Mauritania, Mali, and Niger, giving rise to the possibility of large masses of dust being lifted.…”
Section: Nmmb/bsc-dust Model Forecastsmentioning
confidence: 99%
“…The formation of low‐level jets in the two preferred areas of the SHW is the fundamental cause of most summer dust storm events in the ME (Ali, 1994; Francis et al., 2017; Mofidi & Jafari, 2011). Although we witness different types of dust storms, including frontal (pre‐frontal and post‐frontal), cyclonic, convective, and Shamal dust storms due to different formation mechanisms and synoptic patterns throughout the year (Hamzeh et al., 2021; Karami et al., 2021; Mohammadpour et al., 2021), however, the intraseasonal variation and interannual activity of dust storms in the corridor of eastern Iraq are directly related to the Spatio‐temporal variability of the SSW and its NLLJ core in MP during the summer and at the peak of dust activity (Ali, 1994; Al senafi & Anis, 2015; Najafi et al., 2017; Pye, 1987; Yu et al., 2013, 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The SHW and its regional effects concerning dust activities have been widely studied in the last decades (Ali, 1994;Goudie, 2001;Goudie & Middleton, 2006;Hamzeh et al, 2021;Hassani, 2016;Houseman, 1961;Karami et al, 2021;Mohammadpour et al, 2021Mohammadpour et al, , 2022Notaro et al, 2013;Pye, 1987;Rashki et al, 2019;Yu et al, 2016), whereas the regional-scale circulation that governs the formation and development of SSW is less well understood. In one of the few studies, MEM83 suggested that the SSW is the result of a simultaneous establishment of a semi-permanent high-pressure cell in northern Saudi Arabia, and a trough on the lee of the ZAG, which is connected to heat low over Pakistan and Afghanistan.…”
mentioning
confidence: 99%